2021
DOI: 10.1371/journal.pone.0257961
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community structure of early-stage biofilms is dictated by temporal succession rather than substrate types in the southern coastal seawater of India

Abstract: Bacterial communities colonized on submerged substrata are recognized as a key factor in the formation of complex biofouling phenomenon in the marine environment. Despite massive maritime activities and a large industrial sector in the nearshore of the Laccadive Sea, studies describing pioneer bacterial colonizers and community succession during the early-stage biofilm are scarce. We investigated the biofilm-forming bacterial community succession on three substrata viz. stainless steel, high-density polyethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that the bacterial community in marine plastic litter mainly consisted of α‐proteobacteria and γ‐proteobacteria, followed by Bacteroidota and Actinobacteriota (Denaro et al, 2020; Gao & Sun, 2021; Roager & Sonnenschein, 2019; Vaksmaa et al, 2021; Wright et al, 2021). The results of this report showed that the phylum Proteobacteria, as an early colonizer of unnatural substrate biofilms (Sushmitha et al, 2021), was overwhelmingly dominant in the PET flora, followed by the phylum Bacteroidota (Figure S2). Salinisphaeraceae were more predominant in BC02 and BC06 samples, and Balneolaceae were more predominant in BC06 samples, suggesting that these two families may be involved in PET degradation, but no bacteria from these two families were isolated from the 15 PET‐enriched consortia (Figure 1).…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have shown that the bacterial community in marine plastic litter mainly consisted of α‐proteobacteria and γ‐proteobacteria, followed by Bacteroidota and Actinobacteriota (Denaro et al, 2020; Gao & Sun, 2021; Roager & Sonnenschein, 2019; Vaksmaa et al, 2021; Wright et al, 2021). The results of this report showed that the phylum Proteobacteria, as an early colonizer of unnatural substrate biofilms (Sushmitha et al, 2021), was overwhelmingly dominant in the PET flora, followed by the phylum Bacteroidota (Figure S2). Salinisphaeraceae were more predominant in BC02 and BC06 samples, and Balneolaceae were more predominant in BC06 samples, suggesting that these two families may be involved in PET degradation, but no bacteria from these two families were isolated from the 15 PET‐enriched consortia (Figure 1).…”
Section: Discussionmentioning
confidence: 72%
“…For example, we do not know if all free-living species of bacteria can form biofilms, but it has become apparent that a substantial fraction of bacteria in the environment exists as biofilm [ 66 ]. Moreover, the assembly of mixed species biofilms occurs through a temporal sequence of species additions [ 62 , 64 ], suggesting that primary colonists may establish a pathway for subsequent colonization. In the case of river biofilm communities, Besemer et al, [ 61 ] has shown that the phylogenetic composition of mature biofilm is different and less diverse than the stream community.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we do not know if all free-living species of bacteria can form biofilms, but it has become apparent that a substantial fraction of earth’s bacterial microbiome exists as biofilm (63). Moreover, the assembly of mixed species biofilms occurs through a temporal sequence of species additions (59, 61), suggesting that primary colonists may establish a pathway for subsequent colonization. In the case of river biofilm communities, Besemer et al, (58) has shown that the phylogenetic composition of mature biofilm is different and less diverse than the stream community.…”
Section: Discussionmentioning
confidence: 99%